A phase I trial assessing the safety, pharmacokinetics, cerebrospinal fluid penetrance, and food effect of BTK inhibitor tolebrutinib in healthy volunteers - Marie‐José Cabanis; Olivier Nicolas; Olivier Vitse; Christelle Jan; Priscilla Brun; Patrick Soubayrol; William B. Smith; Timothy J. Turner; Emmanuel Krupka (Wiley, 2024)
Abstract Tolebrutinib is an oral, brain‐penetrant, covalent Bruton's tyrosine kinase inhibitor in development to treat multiple sclerosis at 60 mg/day with food. A phase I trial was conducted in healthy volunteers to assess the safety and pharmacokinetics of tolebrutinib at oral doses higher than 60 mg with food and during fasting, and to determine cerebrospinal fluid (CSF) exposure after a single dose of 60 or 120 mg with food. The trial included double‐blind, placebo‐controlled single ascending dose (120, 240, and 300 mg; fed and fasted) and multiple ascending dose (120, 180, and 240 mg) arms. Additional open‐label cohorts received a single 60 mg dose with a high‐fat meal and during fasting using a crossover design or a single 60 or 120 mg dose with food and lumbar puncture to obtain CSF. Tolebrutinib was rapidly absorbed and converted to an active metabolite (designated "M2"), both of which had a terminal half‐life of ~5 h. Tolebrutinib and M2 exposures increased following administration with food versus fasting, and plasma levels were generally dose proportional. For up to 4 h (the last measurement timepoint) after a 60 mg dose, CSF concentrations of tolebrutinib exceeded its in vitro cellular potency (half‐maximal inhibitory concentration [IC50]) for microglia, and tolebrutinib and M2 surpassed their biochemical IC50. Tolebrutinib was well‐tolerated, and treatment‐emergent adverse events were generally mild. Concentration‐QTc modeling showed no effects on QT/QTc intervals for any tolebrutinib dose or fed status. In conclusion, tolebrutinib has an acceptable safety profile at supratherapeutic doses and achieved bioactive CSF exposures at the phase III dose.